Clinical Characteristics Associated with Poor Prognosis of Acquired Immunodeficiency Syndrome Patients Complicated with Disseminated Talaromycosis marneffei - Wu L; Pan Y; Xu K (Infection and Drug Resistance, 2023)
Lianpeng Wu,1– 3 Yong Pan,1,2 Ke Xu1– 3 1Department of Clinical Laboratory Medicine, The Ding Li Clinical College of Wenzhou Medical University, Wenzhou, 325000, People’s Republic of China; 2Department of Clinical Laboratory Medicine, Wenzhou Central Hospital, Wenzhou, 325000, People’s Republic of China; 3Key Laboratory of Diagnosis and Treatment of New and Recurrent Infectious Diseases of Wenzhou, Wenzhou, 325000, People’s Republic of ChinaCorrespondence: Ke Xu, Wenzhou Central Hospital, Key Laboratory of Diagnosis and Treatment of New and Recurrent Infectious Diseases of Wenzhou, The Ding Li Clinical College of Wenzhou Medical University, No. 252 Baili East Road, Lucheng District, Wenzhou, 325000, People’s Republic of China, Tel +86-13566290303, Email wzxuke72@163.comPurpose: To analyze the clinical characteristics of AIDS with dTSM, especially in patients with poor prognosis.Patients and Methods: One hundred and seventy AIDS patients were enrolled in this single-center retrospective study. The epidemiological characteristics, clinical manifestations, laboratory tests, imaging examination, and treatment outcome were collected. Logistic regression analysis was used to estimate the risk of mortality in AIDS patients with dTSM. The predictive value was evaluated using the receiver operating characteristic (ROC) curve.Results: From 2015 to 2022, the incidence of AIDS with dTSM in the Wenzhou region increased yearly, mainly in young adults. The mortality rate was 16.47%. The most common clinical manifestations were lymph-node enlargement (92.35%) and fever (78.24%). Multivariate logistic regression analysis showed that procalcitonin (PCT), blood urea nitrogen (BUN), shock, and antiretroviral therapy (ART) were the risk factors for poor outcomes. The model comprised four risk factors and showed an excellent prediction performance, with an AUC of 0.987 in the training cohort (95% CI: 0.946– 0.999) and 0.976 in the validation cohort (95% CI: 0.887– 0.999).Conclusion: This study suggested that PCT, BUN, shock, and ART were associated with the prognosis and outcome of AIDS with dTSM and had a specific predictive value.Keywords: acquired immunodeficiency syndrome, Talaromycosis marneffei, clinical characteristics, risk factor, prediction model, poor prognosis